Root traits rather than functional diversity of soil microorganisms respond to drought and plant species composition in Mediterranean shrubland species - Ammar Shihan; Ammar Shihan; Stephan Hättenschwiler; Nathalie Fromin (Frontiers in Forests and Global Change, 2022)
Belowground responses are critical in understanding how plants cope with the predicted increase in drought intensity and frequency in the Mediterranean region, because plant root systems compete with each other and interact with soil microbial communities under limiting water availability. However, the combined responses of plant roots and soil microorganisms to drought are not well understood. Using an experimental approach, we addressed the question of how recurrent drought and different combinations of two individuals from three common Mediterranean plant species (Quercus coccifera, Cistus albidus, and Brachypodium retusum) affect root characteristics and soil microbial activity. We hypothesized that drought effects on root characteristics and associated soil microbial communities are stronger when plant individuals of the same species compete for limiting water compared to inter-specific competition. Root morphological traits were more affected by the species identity of the neighbor individual than by recurrent severe drought, particularly in B. retusum, which may in part explain the higher survival previously observed for this species. On the other hand, drought and plant composition had little effect on root-associated soil microbes’ ability to use a wide range of different carbon substrates. Overall, our results did not confirm stronger effects of intra- compared to interspecific competition on the root and microbial responses, but showed strong species identity effects.